Fuzzy Type RK4 Solutions to Fuzzy Hybrid Retarded Delay Differential Equations - Dhandapani, Prasantha Bharathi; Baleanu, Dumitru; Thippan, Jayakumar; Sivakumar, Vinoth (Frontiers in Physics, 2019)
This paper constructs the numerical solution of particular type of differential equations called fuzzy hybrid retarded delay-differential equations using the method of Runge-Kutta for fourth order.The concept of fuzzy number, hybrid-differential equations and delay-differential equations binds together to form our equations.An example following the algorithm is presented to understand the Concept of fuzzy hybrid retarded delay-differential equations and its accuracy is discussed in terms of decimal places for easy understanding of laymen.